2010
DOI: 10.2215/cjn.08111109
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Development of Hypertension and Proteinuria with Cediranib, an Oral Vascular Endothelial Growth Factor Receptor Inhibitor

Abstract: Background and objectives: Hypertension and proteinuria are common but poorly understood renal toxicities of vascular endothelial growth factor (VEGF) receptor signaling pathway inhibitors. In this phase II study of cediranib (AZD2171) for recurrent epithelial ovarian cancer, the time course and severity of BP changes and proteinuria were characterized.Design, setting, participants, & measurements: 46 women ages 41 to 77 years were treated with cediranib. 26% had baseline hypertension. Twice-daily BP was recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
64
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 35 publications
5
64
0
Order By: Relevance
“…DBP recovered to near baseline during the recovery period, except that DBP was slightly elevated from baseline with the highest dose of cediranib. Clinical studies of VEGF signal inhibitors showed that hypertension was induced within a few days of first administration (Maitland et al, 2009;Robinson et al, 2010a), and recovered following the end of administration (Azizi et al, 2008). Therefore, the trend of hypertension represented in this non-clinical study was similar to that in clinical studies.…”
Section: Resultssupporting
confidence: 74%
“…DBP recovered to near baseline during the recovery period, except that DBP was slightly elevated from baseline with the highest dose of cediranib. Clinical studies of VEGF signal inhibitors showed that hypertension was induced within a few days of first administration (Maitland et al, 2009;Robinson et al, 2010a), and recovered following the end of administration (Azizi et al, 2008). Therefore, the trend of hypertension represented in this non-clinical study was similar to that in clinical studies.…”
Section: Resultssupporting
confidence: 74%
“…These effects have been documented upon administration of several inhibitors of the VEGF signaling pathway, such as bevacuzimab and cediranib (24,25), due to a possible perturbation of endothelial cell function (23). In this present study, hypertension was well managed by antihypertensive agents and proteinuria was managed by dose reductions or delays, and did not cause dose interruptions at the MTD or lower doses.…”
Section: Discussionmentioning
confidence: 48%
“…4,5 For instance, anti-vascular endothelial growth factor (VEGF) therapy is associated with increased incidence of hypertension, proteinuria, and CKD. 6 A better understanding of the renal complications of anti-VEGF therapy has also led to greater understanding of the functioning of the glomerular filter and the pathogenesis of preeclampsia. 7,8 As with anti-VEGF therapy, newer myeloma therapies have also increased survival of patients with CKD.…”
mentioning
confidence: 99%